Concurrent stimulation of monocytes with CSF1 and polarizing cytokines reveals phenotypic and functional differences with classical polarized macrophages. Issue 3 (24th January 2022) - An, Liying; Michaeli, Julia; Pallavi, Prama; Breedijk, Annette; Xu, Xin; Dietrich, Nadine; Sigl, Martin; Keese, Michael; Nitschke, Katja; Jarczyk, Jonas; Nuhn, Philipp; Krämer, Bernhard K; et al.
Abstract: In atherosclerotic lesions, macrophages are exposed to CSFs and various microenvironmental cues, which ultimately drive their polarization state. We studied the expression of different CSFs in artery specimen and cultured vascular cells and assessed whether concurrent stimulation (CS) of monocytes with CSF1 and polarizing cytokines generated macrophages (CSM1 and CSM2) that were phenotypically and functionally different from classically polarized M1 and M2 macrophages. We also assessed the influence of acetylsalicylic acid (ASA) on the capacity of polarized macrophages to stimulate T-cell proliferation. CSF1 was the most prominent CSF expressed in arteries and cultured vascular cells. M1 and CSM1 macrophages differed in CD86 and CD14 expression, which was up-regulated respectively down-regulated by LPS. M2 and CSM2 macrophages were phenotypically similar. Cyclooxygenase expression was different in CSM1 (COX-1 − and COX-2 + after LPS stimulation) and CSM2 (COX-1 + and COX-2 − ) macrophages. TNFα production was more pronounced in CSM1 macrophages, whereas IL-10 was produced at higher levels by CSM2 macrophages. Proliferation of allogeneic T cells was strongly supported by CSM2, but not by CSM1 polarized macrophages. Although ASA did not affect anti-CD3/CD28-mediated proliferation, it significantly reduced CSM2 and CSM1-mediated T-cell proliferation. Supernatants of LPS-stimulated CSM2 but not of CSM1 macrophages could overcome the inhibition by ASA. Hence, we demonstrate that CSM1 and CSM2 macrophages are phenotypically and to some extent functionally distinct from classically polarized M1 and M2 macrophages. CSM2 macrophages produce a COX-1-dependent soluble factor that supports T-cell proliferation, the identity hereof is still elusive and warrants further studies. Graphical Abstract: Concurrent stimulation of monocytes with CSF1 and IL-4 generates polarized M2 macrophages that support T-cell proliferation in a COX-1 dependent manner upon LPS stimulation.